Initializing Mutually Referential Abstract Objects: The Value Recursion Challenge - Syme, Don (Electronic notes in theoretical computer science, 2006)
Mutual dependencies between objects arise frequently in programs, and programmers must typically solve this value recursion by manually filling “initialization holes” to help construct the corresponding object graphs, i.e. null values and/or explicitly mutable locations. This paper aims to augment ongoing theoretical work on value recursion with a description of a semi-safe mechanism for a generalized form of value recursion in an ML-like language, where initialization corresponds to a graph of lazy computations whose nodes are sequentially forced, requiring runtime checks for soundness during initialization in the style of Russo. Our primary contribution is to use the mechanism to develop compelling examples of how the absence of value recursion leads to real problems in the presence of abstraction boundaries, and give micro-examples that characterize how initialization graphs permit more programs to be expressed in the mutation-free fragment of ML. Finally we argue that in heterogeneous programming environments semi-safe variations on value-recursion may be appropriate for ML-like languages, because initialization effects from external libraries are difficult to characterize, document and control.